Pengaruh Pendidikan Karakter dan Disiplin Belajar Terhadap Hasil Belajar Siswa Setingkat Sekolah Dasar - Umar, Hanif; Lisan, Moh Fasikhul (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the influence of character education and learning discipline on student learning outcomes at the elementary school (SD) level. Character education is one of the strategic approaches to shaping students' attitudes, values, and morals, while learning discipline plays an important role in creating consistent and structured learning habits. The method used is a literature review by analyzing various relevant sources of previous research. The source comes from Google Scholar data, namely articles published until the end of 2024. The data was analyzed in a qualitative descriptive manner. The results of the study show that character education has a positive impact on the formation of positive attitudes of students, such as responsibility, honesty, and cooperation, which directly supports the improvement of learning outcomes. On the other hand, learning discipline has been proven to improve concentration, time management, and student motivation in learning. The combination of effective character education and good learning discipline makes a significant contribution to the achievement of optimal learning outcomes. Thus, this study suggests the importance of integrating character education in the curriculum and habituating learning disciplines from an early age to support the success of student learning at the elementary level